2008
DOI: 10.3928/02793695-20081201-08
|View full text |Cite
|
Sign up to set email alerts
|

Equine-Facilitated Psychotherapy with Adult Female Survivors of Abuse

Abstract: This qualitative study examined the stories of 5 women who experienced abuse and participated in equine-facilitated psychotherapy (EFP) as part of their recovery. Anecdotal accounts support the effectiveness of EFP with women who have experienced abuse, but there is a lack of supporting research. This study was designed to examine the effectiveness of EFP in the treatment of women who have experienced abuse. Selection criteria included age, experience of abuse, participation in EFP, and ability to understand E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0
12

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 15 publications
2
11
0
12
Order By: Relevance
“…EAA/Ts apparently serve diverse populations in terms of symptomatology, such as adult female survivors of abuse (Meinersmann, Bradberry, & Roberts, 2008), cancer survivors (Cantril & Haylock, 2007), people who are recovering from trauma (Yorke, Adams, & Coady, 2008), and nursing students (Roberts, Bradberry, & Williams, 2004). However, most of these studies are inconclusive, as they fail to use a control group.…”
Section: Evaluation Studies Demonstrating Eaa/t Benefits For Various mentioning
confidence: 99%
“…EAA/Ts apparently serve diverse populations in terms of symptomatology, such as adult female survivors of abuse (Meinersmann, Bradberry, & Roberts, 2008), cancer survivors (Cantril & Haylock, 2007), people who are recovering from trauma (Yorke, Adams, & Coady, 2008), and nursing students (Roberts, Bradberry, & Williams, 2004). However, most of these studies are inconclusive, as they fail to use a control group.…”
Section: Evaluation Studies Demonstrating Eaa/t Benefits For Various mentioning
confidence: 99%
“…For example, recent qualitative studies suggest that horses are able to project positive feelings, such as compassion and unconditional love, which in turn provide opportunities for corrective emotional experiences. These corrective experiences entail positive reframing of previous negative patterns of behavior, and even transformational or life-changing events (Aardoom, 2007;Esbjorn, 2006;Hallberg, 2008;Held, 2006;Irwin (2001); Meinersmann et al, 2008); Rector (2005); Webb, W. (2002).…”
Section: Horse-human Relationship and Emotional Well-beingmentioning
confidence: 99%
“…For example, Meinersmann, Bradberry, and Roberts (2008) found that women who had experienced abuse during their lives and had participated in EFP/EAP reported that interactions with horses provided opportunities to increase selfefficacy, enhance feelings of empowerment, and develop a sense of trust and support. Similarly, Yorke et al (2008) research with victims of trauma indicated that the impact of the equine-human relationship was beneficial in restoring the trauma survivor's sense of safety, decreasing symptoms of depression, and offering an opportunity for acceptance.…”
Section: Evidence Involving Efp/eap and Victims Of Traumamentioning
confidence: 99%